2016
DOI: 10.1002/cctc.201601096
|View full text |Cite
|
Sign up to set email alerts
|

The Immobilization of a Transfer Hydrogenation Catalyst on Colloidal Particles

Abstract: In this paper, we report a new synthetic procedure to immobilize a transfer hydrogenation catalyst on the surface of colloidal polystyrene particles. Using supports of colloidal dimensions allows for combining a relatively high surface area for catalyst binding, mobility of the catalyst, and facile recovery by centrifugation or sedimentation. The immobilization procedure relies on the covalent attachment of terpyridine moieties on the particle surface. These immobilized terpyridines are subsequently employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This enables multiphasic reactions with moderate to low leaching of metal to the product phase. [18][19][20][21] The difference to the before mentioned systems is that the ligands are covalently bound, making the catalyst less similar to a truly homogeneous catalyst. It should be mentioned, that the selectivity does not necessarily suffer from this, and in some cases even increases.…”
Section: Introductionmentioning
confidence: 99%
“…This enables multiphasic reactions with moderate to low leaching of metal to the product phase. [18][19][20][21] The difference to the before mentioned systems is that the ligands are covalently bound, making the catalyst less similar to a truly homogeneous catalyst. It should be mentioned, that the selectivity does not necessarily suffer from this, and in some cases even increases.…”
Section: Introductionmentioning
confidence: 99%
“…By the modication with other chemicals (e.g. terpyridine) and/or unnatural amino acids related to metal binding, 41,42 peptide probes with improved binding affinity and selectivity may be found.…”
Section: Characterization Of Peptides Exhibiting Different Binding Bementioning
confidence: 99%
“…In particular, ruthenium complexes have been used in several processes as, for example, catalytic hydrogenation ( VAN RAVENSTEIJN et al, 2017), transformation of amines in nitriles (CRISTIAN et al, 2013). It is worthy to note that some ruthenium complexes have been successfully used in solar cells (AMETA; AMETA, 2016; AGHAZADA; NAZEERUDDIN, 2018); In medical research, some studies have shown that ruthenium (II) complexes are useful as a new generation of antitumor drugs (LIN et al, 2018), since they exhibit higher efficiency and lower toxicity when compared to the platinum complexes that are commonly used (ABID; SHAMSI; AZAM, 2016;THOTA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%